Video‐based valve motion combined with computational fluid dynamics gives stable and accurate simulations of blood flow in the Realheart total artificial heart. Issue 1 (20th September 2021) - Kelly, Nathaniel S.; McCree, Danny; Fresiello, Libera; Brynedal Ignell, Nils; Cookson, Andrew N.; Najar, Azad; Perkins, Ina Laura; Fraser, Katharine H.
Abstract: Background: Patients with end‐stage, biventricular heart failure, and for whom heart transplantation is not an option, may be given a Total Artificial Heart (TAH). The Realheart® is a novel TAH which pumps blood by mimicking the native heart with translation of an atrioventricular plane. The aim of this work was to create a strategy for using Computational Fluid Dynamics (CFD) to simulate haemodynamics in the Realheart®, including motion of the atrioventricular plane and valves. Methods: The accuracies of four different computational methods for simulating fluid‐structure interaction of the prosthetic valves were assessed by comparison of chamber pressures and flow rates with experimental measurements. The four strategies were: prescribed motion of valves opening and closing at the atrioventricular plane extrema; simulation of fluid‐structure interaction of both valves; prescribed motion of the mitral valve with simulation of fluid‐structure interaction of the aortic valve; motion of both valves prescribed from video analysis of experiments. Results: The most accurate strategy (error in ventricular pressure of 6%, error in flow rate of 5%) used video‐prescribed motion. With the Realheart operating at 80 bpm, the power consumption was 1.03 W, maximum shear stress was 15 Pa, and washout of the ventricle chamber after 4 cycles was 87%. Conclusions: This study, the first CFD analysis of this novel TAH, demonstrates that good agreement between computational and experimental data can be achieved. This method will therefore enable future optimisation of the geometry and motion of the Realheart®. Abstract : Total artificial heart Realheart TAH, designed to treat heart failure, mimics the human heart's atrioventricular plane displacement. Computational fluid dynamics, incorporating atrioventricular plane and valve motion, was used to simulate device hemodynamics. Four computational methods for simulating fluid‐structure interaction of the valve leaflets were compared with experiments. Motion prescribed from video analysis of experiments was most accurate. At 80 bpm, power consumption was 1.03 W, maximum shear stress 15 Pa, and washout of the ventricle after 4 cycles was 87%.